A highly sensitive non-enzymatic glucose sensor based on CuS nanosheets modified Cu2O/CuO nanowire arrays. (20th February 2020) - Wei, Chenhuinan; Zou, Xiao; Liu, Qiming; Li, Shuxian; Kang, Chenxia; Xiang, Wei
Abstract: CuS nanosheets modified Cu2 O/CuO nanowire arrays (NWAs) were successfully fabricated on Cu foil by in-situ growth and successive ionic layer adsorption and reaction (SILAR) methods without binders. The three-dimensional Cu2 O/CuO NWAs not only showed strong binding force with current collector but also provided abundant surface area to support CuS nanosheets. Different morphologies of CuS were obtained by varying the Cu(NO3 )2 and Na2 S concentrations and the SILAR cycle. When these step-wise prepared products were employed for non-enzymatic glucose sensing, the amperometric response of the optimized CuS/Cu2 O/CuO/Cu electrode was approximately twice of that of Cu2 O/CuO/Cu electrode. The result is attributed to the modification of CuS nanosheets with suitable amount which increases the active surface area of the electrode. This designed electrode presents an ultrahigh sensitivity of 4262 μA mM −1 cm −2 in the range from 0.002 to 4.096 mM, as well as the excellent selectivity, reproducibility and stability. Moreover, due to the facile preparation and the low cost of Cu based sensors, the CuS/Cu2 O/CuO/Cu electrode will be one kind of promising materials for constructing practical non-enzymatic glucose sensors.